Contests and other topics in multi-agent systems - Ghosh, A (Association for Computing Machinery, 2023)
Contests are games where agents compete by making costly and irreversible investments to win valuable prizes. They model diverse scenarios ranging from competition among Bitcoin miners to crowdsourcing. My work has touched upon the following topics in contests theory: (i) design of contests to get a moderate output from many agents rather than a very high output from a few; (ii) design of contests to get higher output from an underrepresented group of agents; (iii) existence, computational complexity, and price of anarchy of equilibria in a model where agents participate in several simultaneous contests; (iv) convergence of best-response dynamics in contests. In addition to the above, my ongoing work focuses on topics in contest theory like learning dynamics in contests and analysis of contests where groups of agents (and not just individual agents) compete to get an outcome that affects all of them. More broadly, I have also worked on the following topics: (i) improved, near-optimal algorithms for restless multi-armed bandits with applications to healthcare; (ii) analysis of coalition formation dynamics for deliberation.